Proinflammatory cytokines and their membrane-bound receptors are altered in the lymphocytes of schizophrenia patients - Pandey, Ghanshyam N.; Ren, Xinguo; Rizavi, Hooriyah S.; Zhang, Hui (Schizophrenia research, 2015)
Abnormalities of protein levels of proinflammatory cytokines and their soluble receptors have been reported in the plasma/serum of schizophrenia (SZ) patients. To examine if SZ is also associated with the abnormal gene expression of cytokines and their membrane-bound receptors, we studied mRNA expression of proinflammatory cytokines and their receptors in lymphocytes of SZ patients and normal control (NC) subjects. We determined the protein and mRNA expression of proinflammatory cytokines and mRNA expression of their receptors in lymphocytes from 30 SZ patients and 30 drug-free NC subjects. The subjects were diagnosed according to DSM-IV criteria. Protein levels of cytokines were determined by ELISA, and mRNA levels in lymphocytes were determined by the qPCR method. We found that the mRNA levels of IL-6, TNF-α, IL-1R1, TNFR1, and TNFR2, but not IL-1β, IL-1R2, IL-1RA, IL-6R, or GP130 were significantly increased in lymphocytes of SZ patients compared with NC subjects. We also found that the protein expression of IL-6 and TNF-α, but not IL-1β, was also significantly increased in SZ patients compared with NC subjects. These studies suggest that in addition to the reported abnormalities of proinflammatory cytokines and their soluble receptors in the plasma of SZ patients, an abnormal gene expression of these cytokines and their membrane-bound receptors may be involved in the pathogenesis of SZ.